PERILAKU MEMILIH PEREMPUAN PADA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA PEKALONGAN TAHUN 2015 (Studi di Kelurahan Kauman dan Kelurahan Panjang Wetan) - Nourmala Farih Ikmaliyani; Priyatno Harsasto (Journal of Politic and Government Studies, 2018)
For a democratic country, society participation about politics is an important thing. One of the society participations is vote in a direct election. Many things affect political behaviour of citizen and there are differences in some areas. Generally, there are three approaches to understand politic behaviour: sociological approach psychological approach, and rational approach. The research will describe women’s politics behaviour in Kauman dan Panjang Wetan urban village, Pekalongan city in the 2015 direct mayor election. The research uses descriptive quantitative method and political behaviour theory. The purpose of this research is to find out how and what is the factor that affect women decide their politics choices.The result of the research is the political behaviour of Kauman and Panjang Wetan urban village same and mostly affected by media, figure of candidate, and community organization. This result refutes many theories that political behaviour of Javanese people esspecially Javanese women is affected by the family and neighbourhood society. Women in these two urban villages have been independent and rasionalistic in direct election. The opinion of head family does not really affected women to participate in election. Intead media mostly affects women political education and how they getting the politics information.Key words: political behaviour, women voting behaviour, political participation.